Electrospun perovskite nano-network for flexible, near-room temperature, environmentally friendly and ultrastable light regulation. (10th December 2022) - Li, Yongliang; Sun, Haoxuan; Li, Zhen; Wang, Min; Guo, Linqi; Min, Liangliang; Cao, Fengren; Tan, Yeqiang; Li, Liang
Highlights: Perovskite-sodium alginate network is proposed for fast and stable light regulation. Lead leakage of perovskite is inhibited to the drinking standard by sodium alginate. The "egg-box" structure of sodium alginate is proved to be valid for lead caging. Cycling stability of over 1200 cycles is successfully demonstrated. For the application of smart window, energy of over 55.5 J m -3 min -1 is saved. Abstract: Light regulation devices are essential for signal modulation, information encryption and energy-saving smart windows. Recently, due to their excellent stimuli-responsive properties, lead halide perovskites have shown great potential. However, the high transition temperature, irreversibility of the phase transition and toxicity of heavy metals make perovskite materials unsuitable for devices related to human activity. Herein, for the first time, a flexible perovskite nano-network is proposed and its application as a smart window is demonstrated. The perovskite-sodium alginate (SA) nano-network showed a 31.6 °C (20% RH) transition temperature and stability over 1200 cycles. The hydrophobic surface and the "egg-box" structure formed by SA make that the lead leakage is only 2.569 ppb, which is much higher than the drinking water standard. This work provides a successful demonstration for energy-efficient buildings and inspires future nontoxic perovskite-based devices through heavy metal control. Graphical abstract: Image, graphical abstract A flexible hybrid SA-perovskite nano-network for automatic light regulation. Pb leakage has been reduced to as low as 2.569 ppb by a strong SA-Pb bond, which meets the drinking water standard (US Federal 40 CFR 141 regulation). Under AM1.5G solar illumination, an energy saving rate of over 55.5 J m -3 min -1 was observed. Thanks to the framework that balanced the volume change, a stable color shift was achieved over 1200 cycles without weakening.